Electrostatic molecular effect of differently charged surfactants on the solubilization capacity and physicochemical properties of salt-caged nanosuspensions containing pH-dependent and poorly water-soluble rebamipide - Jin, Gang; Ngo, Hai V.; Wang, Jie; Cui, Jing Hao; Cao, Qing Ri; Park, Chulhun; Lee, Beom Jin (International Journal of Pharmaceutics, 2022)
In this study, the electrostatic molecular effect of differently charged surfactants on the solubilization capacity and physicochemical properties of salt-caged nanosuspensions (NSPs) containing poorly water-soluble drug was investigated. Anionic rebamipide (RBM) was chosen as a model drug because of its poor water solubility in low pH condition and ionizable acidic forms. Negatively charged sodium lauryl sulfate (SLS) and positively charged cetyltrimethylammonium bromide (CTAB) were selected as surfactants for the preparation of NSPs or in the dissolution medium. Salt-caged NSPs surrounded by NaCl were prepared by the HCl-NaOH neutralization method in the presence of poloxamer 407. Interestingly, the addition of positively charged CTAB in the preparation process or the dissolution media could interfere with the solubilization capacity of salt-caged NSPs containing a negatively charged drug via intermolecular electrostatic attraction. In the presence of positively charged CTAB, the salt-caged NSP was disordered in structure via electrostatic attractive interaction with partially ionizable anionic RBM resulting in changes in the physicochemical properties of the salt-caged NSP such as low drug content, increased particle size, decreased dissolution rate, and the formation of water-insoluble precipitates with rough and irregular crystals. This inhibitory effect of CTAB on the dissolution rate of pure RBM and the salt-caged NSP in pH 6.8 intestinal fluid was pronounced in a concentration-dependent manner mainly owing to the formation of precipitates, so-called poorly soluble complexes. When the salt-caged NSP (F1) was dissolved in DW containing CTAB, the dissolution rate decreased more significantly, dissolving less than 20% within 2 h. Depending on the surfactant charges, the charge density and the initial potential were varied during the dissolution of NSPs in deionized water (DW). In contrast, the negatively charged SLS did not significantly change the physicochemical properties of the salt-caged NSP. For example, the dissolution rate of the salt-caged NSP containing SLS in DW or pH 1.2 gastric fluid remained over 90% for 2 h. Surfactants for the formulation or dissolution media should be chosen carefully because of their effect on the physicochemical properties and solubilization capacity of salt-caged NSPs containing poorly water-soluble and ionizable drugs via electrostatic molecular interactions.
Keywords: Alanine; Cetrimonium; Hydrogen-Ion Concentration; Quinolones; Sodium Chloride; Solubility; Static Electricity; Surface-Active Agents; Water; Differently charged surfactants; Dissolution performance; Electrostatic molecular interaction; Physicochemical properties; Poorly water-soluble rebamipide; Salt-caged nanosuspension